PERAN ORANG TUA DALAM MEMBERIKAN PENDIDIKAN SEKS PADA ANAK USIA 6-13 TAHUN DI DESA SUNGAI KUYUNG KECAMATAN PANCUNG SOAL - Ramadhani, Ramadhani; Efendi, Efendi (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2020)
The purpose of this study is to illustrate the efforts made by parents in providing sex education to children aged 6-13 years. To explain what form of child questions about sex and to explain the obstacles faced by parents in providing sex education to children aged 6-13 years in Sungai Kuyung Kecamatan Pancung Soal Sub-District. This research is field research with descriptive qualitative methods. In the determination of the sample the author uses snowball sampling. The results of the research that has been conducted in Sungai Kuyung River Village are parents trying to provide sex education to the child and answer the child's questions about sex. Here parents play a role in teaching child sex abuse by applying when entering the parent's room by asking permission before entering, teaching how to look at the situation seen by the child. Then parents also avoid the child from free sex by separating the bed between the parent and brother or sister. Parents also explain about sex to their child as much as they can